2019
DOI: 10.1094/pbiomes-12-18-0059-r
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Characterization of Oomycetes Associated with Corn Seedlings in Michigan

Abstract: Corn is a staple feed and biofuel crop with a value close to $3.7 billion dollars for Michigan’s economy. Knowledge about distribution and abundance of seedling pathogens in Michigan corn fields is limited. Here we used a combination of culture-based and next-generation sequencing of soil samples to determine the extent of species associated with diseased corn seedlings and those present in soil. Over 2 years, symptomatic seedlings and associated soil samples were collected from 11 Michigan fields. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 42 publications
5
10
0
Order By: Relevance
“…to seed treatment varies with temperature (Matthiesen et al 2016). Another study by Rojas et al (2019) showed that isolates belonging to clade B are less sensitive to mefenoxam, which is the more active isomer of metalaxyl. It is possible that the conditions in our study (cold and wet) were very conducive for disease development and consequently the efficacy of the seed treatment was reduced.…”
mentioning
confidence: 99%
“…to seed treatment varies with temperature (Matthiesen et al 2016). Another study by Rojas et al (2019) showed that isolates belonging to clade B are less sensitive to mefenoxam, which is the more active isomer of metalaxyl. It is possible that the conditions in our study (cold and wet) were very conducive for disease development and consequently the efficacy of the seed treatment was reduced.…”
mentioning
confidence: 99%
“…sansomeana and P. sojae are sensitive to fungicides (McCoy et al 2021; Noel et al 2019; Rojas et al 2019). Ethaboxam is a newer compound, and other studies have found that both species are highly sensitive (Noel et al 2019; Rojas et al 2019). Ethaboxam was the most effective fungicide to reduce the growth of both species, but sensitivity varied by species.…”
Section: Discussionmentioning
confidence: 99%
“…Our results agree with other studies that P . sansomeana and P. sojae are sensitive to fungicides (McCoy et al 2021; Noel et al 2019; Rojas et al 2019). Ethaboxam is a newer compound, and other studies have found that both species are highly sensitive (Noel et al 2019; Rojas et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in 141 oomycete OTUs in the roots and 460 in soil. We make the generalization that terrestrial oomycetes are primarily parasites of vascular plants [ 49 , 50 ] and those found in our plots are likely to function as plant pathogens.…”
Section: Methodsmentioning
confidence: 99%